Computer Aided Design (CAD) Based Approach for Ship Hull Geometry Modelling from Offset Data Using B-Spline Curves - Ardi Nugoho Yulianto; Sheely Leony Artha Pasaribu; Raybonda Reinaldi Winarko; Roisul Fadli Ahmad; Berlian Arswendo Adietya; Danu Utama; Ardiansyah Musa Efendi; Sapto Wiratno Satoto (Applied Science and Technology on Naval Engineering, 2026)
Indonesia, as an archipelagic country, requires the development of efficient and independent ship design technologies. This study aims to develop a B-spline-based computer aided design (CAD) program for modelling ship hull geometry from offset data and calculating basic hydrostatic parameters. The offset data are defined as fit points at each station and processed to determine the corresponding control points for generating B-spline section curves. The resulting station curves are then arranged along the longitudinal direction to form the hull geometry. Hydrostatic calculations are performed by evaluating the station curves, determining the submerged sections at a specified draft, calculating the submerged sectional areas, and integrating them along the ship length. The calculated parameters include submerged volume, displacement, Longitudinal Center of Buoyancy (LCB), Length of Waterline (LWL), and Waterplane Area (WPA). The developed program is validated using a ship model template from commercial software by comparing both hull geometry and hydrostatic results. The validation shows deviations under 0.2% for the simple curve test and under 0.35% for the hydrostatic parameters of the selected hull model. These results indicate that the developed program has the potential to serve as a local CAD alternative for preliminary hull modeling and basic hydrostatic calculations.